Identification and Characterization of Dpo42, a Novel Depolymerase Derived from the Escherichia coli Phage vB_EcoM_ECOO78 - Guo, Zhimin; Huang, Jing; Yan, Guangmou; Lei, Liancheng; Wang, Shuang; Yu, Ling; Zhou, Liang; Gao, Anchong; Feng, Xin; Han, Wenyu; Gu, Jingmin; Yang, Junling (Frontiers in Microbiology, 2017)
Biofilm formation, one of the most important virulence factors of pathogenic bacteria, protects bacteria against desiccation, antibiotics, phages and host immune responses. However, phage-derived depolymerases show antibiofilm activity and demonstrate great potential to treat infections caused by biofilm-forming bacteria. In this study, the Escherichia coli phage vB_EcoM_ECOO78 was isolated and characterized, and we observed its ability to lyse five out of 34 tested E. coli clinical isolates. The highest phage titre was observed at a multiplicity of infection of 10−5 and a burst size of approximately 74 plaque forming units (PFU)/infection. Electron micrographs indicated that vB_EcoM_ECOO78 belongs to the family Myoviridae. The presence of increasing halos surrounding the lysis plaques formed by vB_EcoM_ECOO78 indicated that this phage may encode a depolymerase. Based on a sequencing analysis, the complete genome of vB_EcoM_ECOO78 was found to be 41,289 bp in size, with a GC content of 53.07%. Additionally, vB_EcoM_ECOO78 has 56 predicted open reading frames, 51 (91.07%) of which are assumed to be functional. A BLAST analysis indicated that ORF42 of vB_EcoM_ECOO78 (Dpo42) has low identity with other reported phage-associated depolymerases. Dpo42 was expressed and purified as a soluble protein using E. coli BL21. The biofilm formation ability of E. coli isolates and the antibiofilm activity of Dpo42 were tested by performing spot assays and using a 96-well micro-titre plate method. Dpo42 degraded the capsular polysaccharides surrounding E. coli and exhibited dose-dependent biofilm-formation prevention activity. Based on these results, Dpo42 appears to be a novel phage-derived depolymerase that represents a new potential strategy for preventing E. coli biofilm formation.